Environmental health risk communication: Concept, principles and challenges - Tran Thi Tuyet Hanh; Hung Nguyen-Viet (2013)
Due to the consequences of approximately 76.9 million liters of herbicides used by the U.S. Army as part of Operation Ranch Hand during the Vietnam War, in conjunction with rapid industrialization, urbanization and economic development in the recent decades, Vietnam now faces various severe environmental health risks. Public health concern and outrage are usually high regarding risks associated with vulnerable groups, including pregnant women and children or risks occurring on large scales. If environmental health risks are not adequately assessed, communicated, and managed, public trust and supports can dramatically decrease. Risk communication can be a beneficial tool especially in the context of mass communication channel development and availability. However, there are also significant challenges. Experiences in recent years has shown that risk communication activities regarding melamine and powdered milk, cholera exposure and shrimp paste, beta-agonists carcinogens in pork, dioxin in the environment, etc. were not conducted in effective ways, resulting in large financial losses and fear in the community. This article introduces the concepts and core principles of environmental health risk communication(hereafter referred to as risk communication), provides some examples of missed opportunities for effective risk communication implementation and analyses their consequences.